Unlocking hope: domino liver transplantation for maple syrup syndrome, a single center experience work carried out at the King Fahad Specialist Hospital - Al Qahtani, Mohammed; Aloufi, Rawan; Gaw, Ethar; Momani, Hammam; Sengupta, Bodhisatwa; Khan, Iftikhar; Hassan, Ibrahim; Bader, Razan; Abdullah, Rehab; Tawfeeq, Mansour; Zidan, Ahmed (Frontiers in Immunology, 2025)
BackgroundMaple Syrup Urine Disease (MSUD) is an autosomal recessive disorder caused by mutations in the BCKDH complex, leading to the accumulation of branched-chain amino acids. Severe cases of MSUD often require liver transplantation (LT) to restore metabolic stability and prevent neurological complications. Domino liver transplantation (DLT) using MSUD livers has emerged as an innovative approach to expand the donor pool, leveraging the fact that MSUD-affected livers can function normally in recipients without developing MSUD due to extrahepatic BCKDH activity.Methods &ResultsThis study retrospectively reviews the experience at King Fahad Specialist Hospital in Dammam, where seven patients with MSUD underwent LT, with their explanted livers subsequently transplanted into seven other recipients. The results demonstrate the feasibility and safety of this approach, with a 100% survival rate for MSUD patients at a median follow-up of 2.9 years. For the domino recipients, the 3-year graft and patient survival rate was 71.4%, with two graft-related fatalities.ConclusionThe study highlights the importance of careful recipient selection, optimal graft-to-recipient weight ratio, and the potential for hybrid dual graft transplantation in cases where graft volume is insufficient. The findings suggest that DLT using MSUD livers is a viable option, particularly in regions with limited deceased donor activity, and should be considered in mature liver transplant programs to address organ shortages.